Determining optimal positive end-expiratory pressure and tidal volume in children by intratidal compliance: a prospective observational study. (January 2022) - Lee, Ji-Hyun; Kang, Pyoyoon; Song, In Sun; Ji, Sang-Hwan; Lee, Hyung-Chul; Jang, Young-Eun; Kim, Eun-Hee; Kim, Hee-Soo; Kim, Jin-Tae
Abstract: Background: Limited data exist regarding optimal intraoperative ventilation strategies for the paediatric population. This study aimed to determine the optimal combination of PEEP and tidal volume (VT ) based on intratidal compliance profiles in healthy young children undergoing general anaesthesia. Methods: During anaesthesia, infants (1 month–1 yr), toddlers (1–3 yr), and children (3–6 yr) were assigned serially to four ventilator settings: PEEP 8 cm H2 O/VT 8 ml kg −1 (PEEP8/VT 8), PEEP 10 cm H2 O/VT 5 ml kg −1 (PEEP10/VT 5), PEEP 10 cm H2 O/VT 8 ml kg −1 (PEEP10/VT 8), and PEEP 12 cm H2 O/VT 5 ml kg −1 (PEEP12/VT 5). The primary outcome was intratidal compliance profile, classified at each ventilator setting as horizontal (indicative of optimal alveolar ventilatory conditions), increasing, decreasing, or combinations of increasing/decreasing/horizontal compliance. Secondary outcomes were peak inspiratory, plateau, and driving pressures. Results: Intratidal compliance was measured in 15 infants, 13 toddlers, and 15 children (15/43 [35%] females). A horizontal compliance profile was most frequently observed with PEEP10/VT 5 (60.5%), compared with PEEP10/VT 8, PEEP8/VT 8, and PEEP12/VT 5 (23.3–34.9%; P <0.001). Decreasing compliance profiles were most frequent when VT increased to 8 ml kg −1, PEEP increased to 12 cm H2 O, or both. Plateau airway pressures were lower at PEEP8/VT 8 (16.9 cm H2 O [2.2]) and PEEP10/VT 5 (16.7 cm H2 O [1.7]), compared with PEEP10/VT 8 (19.5 cm H2 O [2.1]) and PEEP12/VT 5 (19.0 cm H2 O [2.0]; P <0.001). Driving pressure was lowest with PEEP10/VT 5 (4.6 cm H2 O), compared with other combinations (7.0 cm H2 O [2.0]–9.5 cm H2 O [2.1]; P <0.001). Conclusions: VT 5 ml kg −1 combined with 10 cm H2 O PEEP may reduce atelectasis and overdistension, and minimise driving pressure in the majority of mechanically ventilated children <6 yr. The effect of these PEEP and VT settings on postoperative pulmonary complications in children undergoing surgery requires further study. Clinical trial registration: NCT04633720.